Network and discrete location : models, algorithms, and applications - Daskin, Mark S., 1952- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
This Second Edition remains the only hands-on guide to using and developing facility location models. It offers a practice-oriented introduction to model-building methods and solution algorithms complete with software for solving classical problems of realistic size and end-of-chapter exercises to enhance reader understanding. The book introduces readers to the key classical location problems (covering, center, median, and fixed charge); discusses real-world extensions of the basic models used in locating; outlines a host of methodological tools for solving location models; and much more.
4.5.2 Lagrangian Relaxation: An Optimization-Based Heuristic Algorithm for Solving the Maximum Covering Location Model4.5.3 Other Solution Approaches and Example Results; 4.6 An Interesting Model Property or It Ain't Necessarily So; 4.7 The Maximum Expected Covering Location Model; 4.8 Summary; Exercises; 5. Center Problems; 5.1 Introduction; 5.2 Vertex P-Center Formulation; 5.3 The Absolute 1- and 2-Center Problems on a Tree; 5.3.1 Absolute 1-Center on an Unweighted Tree; 5.3.2 Absolute 2-Centers on an Unweighted Tree; 5.3.3 Absolute 1-Center on a Weighted Tree.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Industrial location -- Mathematical models; Discrete location; Industrial location -- Mathematical models; Probabilistic models; BUSINESS & ECONOMICS -- Facility Management; Industrial location -- Mathematical models; Electronic books; Electronic books